2022
DOI: 10.26693/jmbs07.03.241
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Content of Verification and Assessment Tests of Physical Preparedness of Foreign Servicemen

Abstract: The purpose of the work was to study the structure and content of tests of physical training of the armed forces of foreign countries and further development of the test of physical fitness of servicemen, testing its effectiveness in the system of military-professional activities. To solve the goal, the following tasks were formed: to analyze the main components of the guiding documents on the organization and verification of physical fitness of servicemen, their tasks and areas of implementation; to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Authors of many scientific papers argue that success of the military-professional activity and results of professional training of cadets depend on their physical condition level [3,12,24]. The results of the conducted research confirmed the materials of domestic researchers Yu.…”
Section: Connection Of Thesupporting
confidence: 70%
See 1 more Smart Citation
“…Authors of many scientific papers argue that success of the military-professional activity and results of professional training of cadets depend on their physical condition level [3,12,24]. The results of the conducted research confirmed the materials of domestic researchers Yu.…”
Section: Connection Of Thesupporting
confidence: 70%
“…The purpose of the study was to investigate the dynamics of the physical condition of first-year cadets of the higher military educational institutions during the last three years. The hypothesis for our study was the assumption of the authors [23,24] about a significant deterioration in the physical condition of school youth, including candidates for training in military educational institutions, over the past 10-20 years.…”
Section: Connection Of Thementioning
confidence: 99%